TEACHING STRATEGIES TO RAISE AWARENESS OF NON-COMMUNICABLE DISEASES IN SECONDARY SCHOOLS IN BRUNEI DARUSSALAM - Mohammad Noor, Noormah Azrayati Haji; Jaidin, Jainatul Halida (Proceedings of the International Conference on Education, 2017)
To date, non-communicable diseases (NCDs) remain the leading cause of disability and death in most countries, including Brunei Darussalam. As such, various strategies to improve health literacy have been introduced and carried out by both government and non-government agencies throughout the country. One of the on-going strategies is to raise awareness of NCDs among secondary school students through a subject called Food and Nutrition. This paper documents the teaching strategies used by five exemplary Food and Nutrition (FN) teachers in Brunei Darussalam. The aims of this study were to analyse and identify strategies as well as techniques that teachers could use to help students practice healthy lifestyle behaviours. A discussion on the extent to which these teaching strategies were effective in delivering important messages about NCDs is also presented. This study adopted a qualitative approach to research, wherein data were collected mainly through a series of lesson observations. In addition, analysis of teachers’ lesson plans and students’ work were used to obtain richer data. A total of five FN teachers and twenty-five students participated in the study. Overall, all teachers in the study preferred to use teacher-centred teaching strategies and very few teachers made the effort to incorporate student-centred teaching strategies in their lessons. However, it was found that the students were more engaged in lessons that provided opportunities for experiential and collaborative learning. The study makes a strong recommendation for student-centred teaching strategies in promoting healthy lifestyle behaviours among secondary school students. The findings of this study are useful to FN teachers, researchers and policy-makers. The findings serve as precursors to further research and decision-making.